ANALYSIS OF SCIENCE SUBJECT COMPUTER-BASED NATIONAL EXAMINATION RESULT IN PADANG CITY IN 2019 - Yofva Ramadanni B; Arief Muttaqiin (Universe, 2021)
This study describes the achievements of the computer-based national exams on science studies at the junior high school level in 2019 in Padang. This study aims to find out and see how the achievement of computer-based national exams in Padang. Data sources from the website www.hasilun.puspendik.kemendikbud.go.id. The analysis shows that in West Sumatra taking computer-based national exams in 2019 there were 18 districts. Padang city is ranked second with a score of 58.98 with enough categories. in the city of Padang, there are 55 schools participating in the computer-based national exam in junior high school.